Sustainable Tapping of Commiphora wightii (Arnott) Bhandari - Nair, M. N. B.; Bhatt, J. B.; Paradva, Bhagirath R; Fursule, Avi; Raturi, Pankaj Prasad; Verma, Rajesh (European Journal of Applied Sciences, 2024)
Background: Commiphora wightii exudes a yellowish Oleo-gum-resin known as “Guggul” of Commerce. Guggul is used for several disease conditions in Ayurveda like inflammation, gout, rheumatism, obesity, and disorders of lipid metabolism. The traditional guggul tapping methods are unproductive, destructive, and the plant generally dies after tapping for 3 years. Commiphora wightii is listed as threatened plants of India. Objective: To develop a sustainable tapping technique to enhance production of guggul and ensure the survival of the tapped trees. Material and Method: For sustainable tapping of guggul, Michie gollege or Gebung types of knife is used. Ethephon is used as a stimulator for enhancing production of guggul. Result and discussion: Average production of guggul per plant in control and distilled water treated control was 1.7 and 1.3 grams respectively. Average production of guggul per plant tapped after treating with 5.98 per cent ethephon is 25.57 grams. Average production of guggul per plant tapping after treating with 20 per cent of guggul solution is 199.13 grams. These plants treated with guggul solution were died in the second year. The tapping injury from all taped plants healed completely within a month. Conclusion: Sustainable guggul tapping method is proposed using Michie gollege or Gebung types of knife and treatment with appropriate concentration of ethephon. A protocol is suggested. Tapping of guggul plant using ethephon is economically viable model for commercial production of guggul. This method also ensures the survival of the tapped plants. February to April is the ideal time for tapping the guggul.